Reinženiring nacionalno varnostnega sistema - Podbregar, Iztok (University of Maribor Press, 2019)
Reeingeeniring of the National Security System. The transformation of any area of our life and society is the direction in which time, space, changes in technology, demography, environment, law and many others are guided by each of us. The national security system is an area that occupies an extremely important place of activity within the country. Due to the strengths of the environment (wider and narrower), the system has in the past been under the tiny eye of possible and probable changes, yet in the present day they continue to create a place for the need for a more complete and profound reeingeeniring. The monograph in front of you, present to the lesser and more demanding reader the important frameworks of the national and international security environment, and hopefully arouse the desire for change where needed. The integrity of the text, the inevitability of the meaning of the field and the clarity of the guidelines covered by the structured chapters give guidance to those who are and will be responsible for the national security and national security system. Let them be the starting point and serious reflection from the direction of reeingeeniring.